PERAN BRAND IMAGE MEMEDIASI PENGARUH KUALITAS PRODUK TERHADAP NIAT BELI ULANG (Studi pada Smartphone Samsung di Kota Denpasar) - Hery Suartama, I Ketut Catur; Setiawan, Putu Yudi (E-Jurnal Manajemen; Vol 8 No 4 (2019)DO - 10.24843/EJMUNUD.2019.v08.i04.p24, 2019)
The purpose of this study was to determine the role of brand image in mediating the effect of product quality on repurchase intention. The number of samples is 105 respondents.. The sampling method was determined by a purposive sampling method based on certain considerations, namely, the education level of at least high school / equivalent, had bought Samsung smartphone products, found out information about Samsung smartphone products, and lived in the city of Denpasar. Primary data was obtained by distributing questionnaires and analyzed using SEM (Structural equation modeling) data analysis based on component or variance, namely PLS (Partial Least Square). The results of data analysis show that product quality has a positive and significant effect on brand image, product quality and brand image have a positive and significant effect on repurchase intention, brand image is able to mediate the effect of product quality on repurchase intention.